2001
DOI: 10.1097/00007890-200107150-00024
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Specific Alloantigens in Miniature Swine1

Abstract: These findings support the concept that skin expresses immunogenic alloantigens that either are not expressed or are not immunogenic in cardiac or hematopoietic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 14 publications
5
30
0
Order By: Relevance
“…To further test the possibility that mixed chimeras may have effective direct but not indirect tolerance to donor antigens, we created BALB/c plus CB6F1 into B6 mixed chimeras. In this way the population of recipient T cells in mixed chimeras that normally recognizes donor BALB/c antigens only via indirect presentation on recipient MHC, would also recognize these antigens presented directly [29] on the F1 donor cells. Even though BALB/c hematopoietic cell antigens could be presented directly in the context of both donor and recipient MHC, these chimeras also rejected BALB/c donor skin (Fig.…”
Section: Direct and Indirect Tolerance To Hematopoietic Cells But Notmentioning
confidence: 99%
“…To further test the possibility that mixed chimeras may have effective direct but not indirect tolerance to donor antigens, we created BALB/c plus CB6F1 into B6 mixed chimeras. In this way the population of recipient T cells in mixed chimeras that normally recognizes donor BALB/c antigens only via indirect presentation on recipient MHC, would also recognize these antigens presented directly [29] on the F1 donor cells. Even though BALB/c hematopoietic cell antigens could be presented directly in the context of both donor and recipient MHC, these chimeras also rejected BALB/c donor skin (Fig.…”
Section: Direct and Indirect Tolerance To Hematopoietic Cells But Notmentioning
confidence: 99%
“…Using the approach of combined organ and bone marrow transplantation in hosts conditioned with nonmyeloablative regimens, tolerance has been achieved in rodents, monkeys, mini-swine, and, more recently, in humans (2-7). However, in some studies acceptance of the marrow transplants as judged by the development of mixed chimerism was associated with the rejection of skin grafts or heart grafts (5,8). Initial reports of radiation chimeras that rejected donor skin grafts suggested that skin-specific transplantation Ags explained the rejection, since the infusion of epidermal cells into chimeras resulted in skin graft acceptance (9,10).…”
Section: Immune Tolerance To Combined Organ and Bone Marrow Transplanmentioning
confidence: 99%
“…However, there is considerable variability of skin and s.c. myocardial graft acceptance in mixed chimeras depending upon the host-conditioning regimen that is used, the level of donor T cell chimerism achieved, and the time interval between transplantation of the donor bone marrow/hemopoietic progenitor cells and the organ graft (2,3,11,12). In some studies, there is uniform acceptance of these organ grafts (2,3,11) and in others the majority of the organ grafts are rejected despite high levels of chimerism (5,12).…”
Section: Immune Tolerance To Combined Organ and Bone Marrow Transplanmentioning
confidence: 99%
“…Rather, p21−/− recipients mounted an exaggerated Th1 response relative to WT mice which was associated with accelerated graft rejection (Table I) and exacerbated graft pathology (Figure 1). These differences in the in vitro and in vivo scenarios are likely reflected by the fact that there are clear microenvironmental differences present in vivo following transplantation with differential expression of antigens and compartmentalization of responses that may occur (18)(19)(20)(21)(22)(23)(24)(25). However, the in vivo correlate clearly contains the most relevance as this is most important clinically and reflects the net effect of all of the above variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that immune responses initiated in vitro may not accurately reflect the complexity of responses initiated in vivo where compartmentalization, microenvironmental parameters, and tissue specific expression of antigens may impact outcome (18)(19)(20)(21)(22)(23)(24)(25). Therefore we assessed the ability of WT and p21−/− mice to mount proliferative and cytokine responses following cardiac transplantation.…”
Section: Impact Of P21 On In Vivo T Cell Responses Following Transplamentioning
confidence: 99%